CONTEMPORARY U.S. FOREIGN POLICY TOWARDS BAHRAIN: MAIN INTERESTS AND MECHANISMS OF IMPLEMENTATION - Arsen Vyacheslavovich Gukasov (Современная наука и инновации)
Despite the fact that at the present stage the United States is reviewing its own place in the world political system and, as a result, its own global strategy.